Forest Management in the Interface: Who Are Interface Landowners - Bruce Hull; Sarah F. Ashton; Rien M. Visser; Martha C. Monroe (EDIS, 2008)
Circular 1527, an 11-page illustrated document by Bruce Hull, Sarah F. Ashton, Rien M. Visser, and Martha C. Monroe, characterizes the growing numbers of new interface residents in the south who are shaping the future of forestry. Includes references. Published by the UF School of Forest Resources and Conservation, August 2008.